2014
DOI: 10.1590/1676-060320140615183046
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of riffle beetle assemblages (Coleoptera, Elmidae) in montane rivers of Southern Brazil

Abstract: ., SPIES, M.R., PIRES, M.M. Diversity and distribution of riffle beetle assemblages (Coleoptera, Elmidae) in montane rivers of Southern Brazil. Biota http://dx.doi.org/10.1590/1676-060320140615183046Abstract: The diversity and spatio-temporal distribution of Elmidae (Coleoptera) assemblages in montane rivers and streams of southernmost Brazil (Rio Grande do Sul state) were studied. Six genera were found, represented mostly by larval specimens. Austrolimnius and Macrelmis are new occurrences in the region. Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 35 publications
0
20
0
3
Order By: Relevance
“…Coarse inorganic substrates, such as cobbles and gravel, allow the growth of micro algae and periphyton (Príncipe et al ), favoring the occurrence of scrapers (Merritt & Cummins 1996). Richer riffle beetle communities have also been recorded in other southern Brazilian streams characterized by cobble substrates (Braun et al ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Coarse inorganic substrates, such as cobbles and gravel, allow the growth of micro algae and periphyton (Príncipe et al ), favoring the occurrence of scrapers (Merritt & Cummins 1996). Richer riffle beetle communities have also been recorded in other southern Brazilian streams characterized by cobble substrates (Braun et al ).…”
Section: Discussionmentioning
confidence: 75%
“…Samplings conducted in winter and summer seasons were pooled, according to each sampling unit. This procedure helped increase the number of individuals of each sampling unit as the influence of season on richness and abundance in the southern Brazilian riffle beetle communities is not yet clear (Braun et al ). A total of 36 sampling units were used, corresponding to samplings conducted in each of the three substrate types (stone, gravel and litter), from each of the four buffer strips (1, 2, 3 and 4), in each of the three streams studied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Riffle beetles (Elmidae) are coleopterans that inhabit lotic systems with well-oxygenated waters with strong currents during the larval and adult stages (Brown 1987, Passos et al 2003a, b, Couceiro et al 2007, Elliott 2008, Braun et al 2014a and commonly found in well-preserved streams (Braun et al 2014b). Some genera have been associated with streams running through well-preserved and sometimes large forested areas (Weigel et al 2003, Iñiguez-Armijo et al 2014, while others seem to be tolerant to forest conversion and can be abundant in deforested streams (Paula and Fonseca-Gessner 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Elmins are aquatic insect species that are sensitive to various pollutants such as agricultural, industrial and household waste. These species are reported to be clean water indicators due to their high sensitivity to pollutants (Braun et al 2014, Taşar, 2018a. The Heteroceridae family is known to have 200 species of 5 genera worldwide (Mascagni, 1995;Taşar, 2014a).…”
Section: Aquatic Insectsmentioning
confidence: 99%